Answer:
The roots of the quadratic equation are.
t = -0.78
t = -4.62
Explanation:
Assume: we find the roots of the given quadratic equation.
Given:
the given expression is.
T squared plus 5.4t plus 3.6 equals 0
Rewrite the equation as.
![t^(2)+5.4t+3.6=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6kywflb6rcdjbh1479ejcjslyrula167ws.png)
Now, we first find the root of the above equation.
Use quadratic formula with
.
![t=\frac{-b\pm \sqrt{(b)^(2)-4ac}}{2a}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/et07icr7cistqg2npferedd1uan2dnjsjn.png)
Put a, b and c value in above equation.
![t=\frac{-5.4\pm \sqrt{(5.4)^(2)-4(1)(3.6)}}{2(1)}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3eqmi86y3c3zv1psivq1lhq49krfc0ygee.png)
![t=(-5.4\pm √(29.16-4* 3.6))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tlrkrjk5qke6egn3xgnk9clmqj0bit1bhr.png)
![t=(-5.4\pm √(29.16-14.4))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zb7og902p1emrbqoj1vvrzm4odz3gfz9de.png)
![t=(-5.4\pm √(14.76))/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v68fb91y80kplaxejs7yz9465b69eiiktv.png)
![t=(-5.4\pm 3.84)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/l6t4ln05njnb2apfjhk33unfd8fqqjb7tg.png)
For positive sign
![t=(-5.4 + 3.84)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/uhr02pe7qdp37hv8bq917366kfux9ibzra.png)
![t=(-1.56)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y0w046djaz0ulefgalclevxra8uou32gqj.png)
t = -0.78
For negative sign
![t=(-5.4 - 3.84)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5uq6tgr8qmdx8d2yo9udeb2pwqjpdyle5a.png)
![t=(-9.24)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9z30mvsb0c9ocrqv1sh0qrjzvhqp0h15cl.png)
t = -4.62
Therefore the roots of the quadratic equation t = -0.78 or t = -4.62
.